Relationship between soil organic matter and nematodes in sugarcane fields - Patricia Angelo Barros; Elvira Maria Regis Pedrosa; Mércia Soares de Oliveira Cardoso; Mario Monteiro Rolim (Semina: Ciências Agrárias, 2017)
Sugarcane plays an important socio-economic role in northeastern Brazil. However, the low yield in this region is associated with several factors (e.g. frequent occurrence of plant-parasitic nematodes). In order to observe the influence of soil organic matter on the nematodes, this study aimed to characterize the spatial nematode distribution in a sugarcane field. The study was carried out in Goiana - Pernambuco State (Brazil), fifty days after sugarcane cutting (10 days after vinasse application). The sampling scheme consisted of a regular 60 × 50-m grid, 10 m spaced, through 0 to 0.2 m depth. Spatial distribution was evaluated by semivariograms fit and performed by ordinary kriging interpolation for mapping. Exponential and spherical models promoted the best fit to semivariograms, resulting in ranges from 16 to 19 m. There was a strong negative correlation between soil organic matter and plant-parasitic nematode population density. Free-living nematodes had a similar distribution pattern as soil organic matter content. These results indicated that soil organic matter had important effects on spatial distribution of both plant-parasitic and free-living nematodes.